İLAHİ DİNLERİN HEDEFLEDİĞİ İDEAL İNSAN - ŞAĞBANŞUA, SEVİNÇ (Fırat Üniveristesi, 2006)
İnsan, maddi ve manevi yönüyle en güzel şekilde yaratılmıştır. Birbirine zıt pekçok eğilimleri olan insan, İlahi vahiyle desteklenmek suretiyle her zaman iyiliğeyönlendirilmiştir. Bu yardımlar vasıtasıyla ondan, hatalarını fark edip davranışlarınıdüzeltmesi ve ilahi mesajlarda belirtilen ölçülerde ideal bir insan olması istenmiştir. Buçalışmamızda; Tevrat, İncil ve Kur'an-ı Kerim açısından ideal insanla ilgili tespitleryapmaya ve ideal insanın, ilahi dinler noktasında ortak yönlerini ortaya koymayaçalıştık.Anahtar kelimeler: İdeal insan, Yahudilik, Hıristiyanlık, İslamiyet

Mankind is created in perfect manner both physically and spiritually. Havingalot of tendencies opposing eachother, mankind is always guided towards the goodnessby the support of the Creator in the form of divine apocalypse. Through these supportshuman-being is expected to realize his mistakes and become the ideal person that isdescribed in divine messages. The aim of this study is to analyze the ideal person interms of Tora (Old Testament), Bible, and Qur?an and to point out the charateristics ofthe ideal person that are common to all three divine religions.Keywords: Ideal human, Judaism, Christianity, Islam
Ideal human in divine religions
Keywords: Din